An analysis of eight grade students mathematical reasoning in mean, median, and mode - N Arsoetar; S Sugiman (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
This paper reports on the level of mathematical reasoning of eighth grade students. The study involved 31 eight grade junior high school students in urban areas in Wonosobo. The data collection used the test in the form of a description problem developed with scoring guidance in accordance with the assessment rubric that has been made. Technique of data analysis in this research by give score on each answer and convert become standard value five criterion. The results showed that the majority of students' mathematical reasoning are at an intermediate level. Thus, students need to be accustomed to solving problems that make their mathematical reasoning abilities improved.